Eag1 K+ Channel: Endogenous Regulation and Functions in Nervous System. (6th March 2017) - Han, Bo; Tokay, Tursonjan; Zhang, Guangming; Sun, Peng; Hou, Shangwei
Abstract : Ether-à-go-go 1 (Eag1, Kv10.1, KCNH1) K + channel is a member of the voltage-gated K + channel family mainly distributed in the central nervous system and cancer cells. Like other types of voltage-gated K + channels, the EAG1 channels are regulated by a variety of endogenous signals including reactive oxygen species, rendering the EAG1 to be in the redox-regulated ion channel family. The role of EAG1 channels in tumor development and its therapeutic significance have been well established. Meanwhile, the importance of hEAG1 channels in the nervous system is now increasingly appreciated. The present review will focus on the recent progress on the channel regulation by endogenous signals and the potential functions of EAG1 channels in normal neuronal signaling as well as neurological diseases.